Optimizing Academic Skills in International Relations Students through ESP: A Focus on Information Sharing with Active and Passive Voice - Andi Anugrah Surya Ardhy; Sri Hartiningsih (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2023)
This research uses a qualitative approach to explore academic information-sharing skills among International Relations study program students. Through interviews with lecturers and students and classroom observations, this research observes interactions in learning English for Specific Purposes (ESP) with a focus on teaching active and passive sentences. By applying the Miles and Huberman model analysis, this research found that teaching active and passive sentences in the ESP approach had a positive and significant impact on the development of various skills, including information sharing, communication, writing, conceptual understanding, critical thinking, as well as student participation and interaction skills, in the context of studying International Relations. This approach also creates a collaborative learning environment where students actively participate in discussions, interact with lecturers and fellow students, and share experiences and knowledge related to learning material. The results of this research consistently support the effectiveness of teaching active and passive sentences in the ESP approach in improving communication, writing, critical thinking skills, and student participation and interaction in the context of learning International Relations. The implications of this research can be the basis for developing curriculum and teaching methods that are more effective in enriching ESP learning for International Relations students.